5
$\begingroup$

I am struggling to derive a first order in this model with Cobb-Douglas production function and CES labour aggregator with two types labour (here male and female, but could be equally low and high skill).

Setup: Cobb-Douglas production function $$ Y = A K^{\alpha}L^{(1-\alpha)} \tag{1}\label{1} $$ where $K$ is capital and $L$ is labor, and $A$ the TFP. There are two types of labor $i \in \{F,M\}$ that are aggregated with constant elasticity of substitution $$ L = \left[(1-\lambda) (a_M M)^{\frac{\sigma-1}{\sigma}} +\lambda(a_F F)^{\frac{\sigma-1}{\sigma}} \right]^{\frac{\sigma}{\sigma-1}} \tag{2}\label{2} $$ where $\sigma$ represents elasticity of substitution between $M$ and $F$, $a_M$ and $a_F$ are productivity terms, and $\lambda$ is the share parameter. Combining these two equations gives $$ Y = A K^{\alpha} \left[(1-\lambda) (a_M M)^{\frac{\sigma-1}{\sigma}} +\lambda(a_F F)^{\frac{\sigma-1}{\sigma}} \right]^{\frac{(1-\alpha)\sigma}{\sigma-1}} \tag{3}\label{3} $$

Solution: Setting marginal products of labour equal to wage should give $$ W^{F} = (1-\alpha)\lambda a_F A K^{\alpha} (a_FF)^{-\alpha} \times \left[ (1-\lambda) \left( \frac{A_MM}{a_FF}\right)^{\frac{\sigma-1}{\sigma}}+\lambda \right]^{\frac{(1-\alpha)\sigma}{\sigma-1}-1} \tag{4.1}\label{4.1} $$ $$ W^{M} = (1-\alpha)(1-\lambda) a_M A K^{\alpha} (a_MM)^{-\alpha} \times \left[ (1-\lambda) \left( \frac{A_FF}{a_MM}\right)^{\frac{\sigma-1}{\sigma}} \right]^{\frac{(1-\alpha)\sigma}{\sigma-1}-1} \tag{4.2}\label{4.2} $$

Steps: So, I wanted to get the foc of equation $ \eqref{3} $ to get the marginal product of each type of labor and doing double chain rule for each powered bracket, but my result seems not to simplify to what it should. $$ \frac{\partial Y}{\partial F} = (1-\alpha) \lambda a_F A K^{\alpha} (a_FF)^{\frac{-1}{\sigma}} \times \left[(1-\lambda) (a_MM)^{\frac{(\sigma-1)}{\sigma}} + \lambda(a_FF)^{\frac{(\sigma-1)}{\sigma}} \right]^{\frac{(1-\alpha)\sigma}{\sigma-1}-1} $$

Edit: Edited the FoC for the mistake. And to close this, I am putting here the simplification as suggested in the answer (hopefully without typos): $$ = (1-\alpha) \lambda a_F A K^{\alpha} (a_FF)^{\frac{-1}{\sigma}} \times \left[\left((1-\lambda) (a_MM)^{\frac{(\sigma-1)}{\sigma}} + \lambda(a_FF)^{\frac{(\sigma-1)}{\sigma}}\right) \times \frac{(a_FF)^{\frac{(\sigma-1)}{\sigma}}}{(a_FF)^{\frac{(\sigma-1)}{\sigma}}} \right]^{\frac{(1-\alpha)\sigma}{\sigma-1}-1} $$

$$ = (1-\alpha) \lambda a_F A K^{\alpha} (a_FF)^{\frac{-1}{\sigma}} \times \left[(1-\lambda) \left(\frac{A_MM}{a_FF}\right)^{\frac{\sigma-1}{\sigma}}+ \lambda \right]^{\frac{(1-\alpha)\sigma}{\sigma-1}-1} \times (a_FF)^{\frac{1-\alpha \sigma}{\sigma}} $$

$$ = (1-\alpha)\lambda a_F A K^{\alpha} (a_FF)^{-\alpha} \times \left[ (1-\lambda) \left( \frac{A_MM}{a_FF}\right)^{\frac{\sigma-1}{\sigma}}+\lambda \right]^{\frac{(1-\alpha)\sigma}{\sigma-1}-1} $$

Sources: Cahuc, P., Carcillo, S., & Zylberberg, A. (2014). Labor economics. MIT press. Chapter 3

Acemoglu, D., Autor, D. H., & Lyle, D. (2004). Women, war, and wages: The effect of female labor supply on the wage structure at midcentury. Journal of political Economy, 112(3), 497-551.

$\endgroup$
4
$\begingroup$

Simply multiply and divide one $\left(a_{F} \boldsymbol{F}\right)^{\frac{(\sigma-1)}{\sigma}}$ in the bracket and then take one outside the bracket. And by the way your FOC is incorrect in that $\frac{\sigma}{(\sigma-1)}$ should be cancelled out.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.